Learning Mathematics through Students’ Worksheets with Open-Ended Approach: A Students’ Errors Analysis on Mathematical Problem-Solving Ability - Wulanningtyas, Melania Eva; Arfin, Arfin; Linling, Yudiani; Setiana, Dafid Slamet; Boriboon, Gumpanat (Jurnal Pendidikan MIPA, 2024)
Open-ended approach has a valuable impact in supporting students’ mathematical problem solving ability. This approach allows students’ to explore different ways in solving mathematical problems, not only focusing on one solution but also considering other alternatives. However, students inevitably make mistakes in solving the problems in their learning process. Therefore, it is important to analyze the errors made by students in mathematics learning using student worksheets with an open-ended approach. This research is a descriptive qualitative study conducted in 6 Private National Junior High Schools in Yogyakarta. These schools were randomly selected using a spinning wheel from 13 schools in the third quartile. The subjects of this study were 384 students selected from 12 classes out of 22 classes in all the research schools. Data were collected using a problem-solving ability test on the subject of systems of linear equations in two variables and interviews. Student errors were categorized based on Newman's Error Analysis, which includes: (1) reading errors, (2) comprehension errors, (3) transformation errors, (4) process skill errors, and (5) encoding errors. The results of this study show that the dominant error sequence made by students is process skill errors, reading errors, comprehension errors, transformation errors, and encoding errors. These errors are caused by students' inaccuracy in calculations, difficulties in calculations, errors in reading the questions, comprehension errors in understanding the given mathematical problems, errors in translating the information provided in the questions, and errors in concluding the problem-solving results due to students not understanding the question instructions properly, and the given mathematical problems being unfamiliar to the students         Keywords: student errors, student worksheet, open-ended approach, problem-solving skills.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp468-485